Effect of problem-based learning approach on students’ achievement in trigonometry - Limann Kwashie Amedume; Hamidu Ibrahim Bukari; Romuald Koffi Mifetu (SAINTIS Publishing, 2022)
This study investigated the effect of the problem-based learning approach on students’ achievement in Trigonometry in Senior High Schools in the Hohoe Municipality of Volta region in Ghana. The research was a mixed method that employed a quasi-experimental non-equivalent comparison group design to compare the achievements of students exposed to a problem-based learning approach and that of the traditional approach. A convenient sampling technique was used to select two Senior High Schools in the Hohoe Municipality which served as comparison and experimental groups respectively. Data was collected using instruments such as questionnaires, trigonometric achievement tests, and semi-structured interviews. A sample of 94 students comprising of 45 in the comparison group and 49 in the experimental group was used for the study. The findings revealed that the problem-based learning approach is very effective for teaching and learning of trigonometry since it promoted students’ active participation in the instructional process, content mastery and improved their creative thinking and independent problem-solving skills.